Mild hypothermia for intracranial aneurysm surgery - Gál, Roman; Smrčka, Martin (Bratislavské lekárske listy, 2008)
BACKGROUND: Eighty nine patients with established intracranial aneurysm (Hunt-Hess score 1 to 3), who were operated at The Department of Neurosurgery, University Hospital Brno in 2003-2006, were enrolled in to the study group. METHODS: After introduction of anesthesia, we started cooling with two circulating-water mattresses (Blanketrol III, Cincinnatti Sub Zero). Body temperature was maintained at 34 degrees C during preparation of cerebral vessels. Active rewarming was started after clip putting. Cooling rate was 0.9 +/- 0.3 degree C per hour and rewarming rate was 0.7 +/- 0.3 degrees C per hour. The required core body temperature was achieved in all patients, i.e. in 100% of cases. Measured values of both esophageal and bladder temperature were not significantly different (p = 0.4475). No significant difference was found when preoperative coagulation parameters and values measured during managed hypothermia were compared. Neurological condition was evaluated as good in 82 patients (92%). Two patients died and one patient was in vegetative status. CONCLUSION: When compared with similar group of patients, who underwent surgery in 1998 to 2002, where good treatment results were achieved in 80%, final good neurological treatment results increased statistically significantly by 12% due to managed hypothermia as well (p = 0.0086) (Tab. 4, Ref. 11).
Keywords: Female; intrakraniální aneurysma; Clinical Trials as Topic; financování organizované; Humans; ženské pohlaví; mužské pohlaví; Male; lidé; Middle Aged; lidé středního věku; Hypothermia, Induced; Financing, Organized; terapeutická hypotermie; Intracranial Aneurysm; klinické zkoušky jako téma